Opto-electro-mechanical properties of lead-free hybrid double perovskites Cs2AgSbX6 (X = Cl, Br, I) for solar cells: A first-principles study. (October 2022) - Babaei, Maryam; Ahmadi, Vahid; Darvish, Ghafar
Abstract: Due to the non-toxicity and better stability compared to perovskites containing lead, the Pb-free halide double perovskites have attracted the attention of many researchers for optoelectronic and photovoltaic applications. In the present study, we use first-principles density functional theory (DFT) calculation to investigate the mechanical, electronic, and optical properties of lead-free halide double perovskites Cs2 AgSbX6 (X = Cl, Br, I) to explore their photovoltaic and optoelectronic applications. PBEsol approximation is used to estimate the shear modulus, Young's modulus, bulk modulus, Poisson's ratio, and some thermodynamic parameters (e.g., Debye temperature) of the compounds. Drawing 3-dimensional representations of Young's modulus and shear modulus, we describe the anisotropic nature of the mechanical parameters of these structures. These compounds have ductility and mechanical stability, according to the computed elastic constants. The examined perovskites exhibit lower bulk modules which makes them better candidates for easier thin film deposition. The bandgap results by the hybrid PBE0 functional are as follows: 2.25 eV for Cs2 AgSbCl6, 1.63 eV for Cs2 AgSbBr6 and 1.07 eV for Cs2 AgSbI6 . These results are consistent with experimental results (unlike the GGA-PBEsol and HSE06 approaches). As these materials have a high absorption coefficient (in the range of 10 4 -10 5 cm −1 for the visible light), and high dielectric constant, they are promising candidates to be used in numerous optoelectronic fields (e.g., solar cells). The trade-off between optical absorption coefficient and mechanical stability of the considered materials indicates that double perovskites Cs2 AgSbBr6 is a promising Pb-free halide semiconductor for solar cell application. Graphical abstract: Image 1 Highlights: Calculating bandgap of double perovskites Cs2 AgSbX6 (X = Cl, Br, I) using PBE0, HSE06, and GGA-PBEsol, PBEsol + SOC methods. Using Sb instead of Bi to lower the bandgap in double perovskite Cs2 AgBiX6 . Mechanically the Cs2 AgSbX6 (X = Cl, Br, I) are in ductile classifications. Investigation of phonon dispersion band structures for dynamical stability of considered materials. Comparison of mechanical and optical properties of Pb-free double perovskite with 3D perovskite MAPbI3 . Introduction of Cs2 AgSbBr6 as a non-toxic, environmentally friendly perovskit for solar cells.